Privacy Preservation on Online Social Networking Issues and Challenges - Maheswari, Uma; Balaji, S (International Journal of Computer Sciences and Engineering, 2025)
Over the past few years, the popularity of social networking sites (SNS) has increased immensely. In the internet age, these social networking sites like Facebook, Twitter, Orkut, LinkedIn, MySpace, etc not only offer the scope of connecting also offers the scope of getting updates at any possible hour of the day. Online networks provide significant advantages both to the individuals and in business sectors. Many users provide information about themselves on social network which can be searched and hacked by the strangers. Thus, it raises privacy and security issues. Unfortunately many users are not aware of this.This paper elaborates Privacy issues concerned with social networking and proposes a framework to deal with. In this paper, study is made on how the current privacy plays on social network sites, how personal information is being influenced by internet and social network, and also how the privacy become a risk and how to employ security awareness to avoid privacy risk.